Analisis Pengaruh Dana Desa, Alokasi Dana Desa Dan Program Pembangunan Desa Terhadap Kesejahteraan Masyarakat Desa Lendola Kecamatan Teluk Mutiara Kabupaten Alor - Syafrudin, Rustini; Tang, Sefnat Aristarkus; Sabu, Junius Menase Sau; Maro, Yustina (Peneliti.net, 2023)
Welfare is a condition in which a person or society is safe, prosperous, safe from all kinds of disturbances, problems or difficulties, and so on. This study aims to determine the influence of Village Funds, Village Fund Allocations and Development Programs on the Welfare of the People of Lendola Village, Teluk Mutiara District, Alor Regency.This type of research is quantitative research with a population of 36 people and a sample of 45 respondents. Data collection techniques are observation, interviews, and literature study. This study uses primary data and the statistical method used in this study is multiple linear regression with a significant t test and a significant F test as a benchmark for taking the hypothesis.The results of this study indicate that: (1). partially the Village Fund has a significance value of 0.000 or 00.0%, where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H1 which states that the Village Fund variable has a partial effect on the Welfare of the Lendola Village Community Teluk Mutiara District, Alor Regency. (2). partially the Village Fund Allocation has a significant value of 0.000 or 0.00% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H2 which states that the Village Fund Allocation variable has a partial effect on Village Community Welfare Lendola Teluk Mutiara District, Alor Regency. (3). Partially the village development program has a significant value of 0.000 or 0.00% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H3 which states that the variable village development program has a partial effect on the Welfare of Village Communities Lendola Teluk Mutiara District, Alor Regency. 4). simultaneously the Village Fund variable, Village Fund Allocation and Development Program have a significant value of 0.000b or 00.0% where this value is smaller than the alpha value which is equal to 0.05 which is 5% so that the results of this study simultaneously receive H4 which states that variable Allocation of Village Funds, Development Program simultaneously influence the Welfare of the Lendola Village Community, Teluk Mutiara District, Alor Regency.